The emergence of insect resistance in Bt-corn: implication of resistance management information under uncertainty - Linacre, Nicholas A.; Thompson, Colin J. (International Food Policy Research Institute, 2005)
The successful management of transgenic technology is likely to depend on the economic behavioral response of farmers to the regulated use of transgenic crops. A well-studied example is the widespread use of Bt-corn, in the United States, and elsewhere, to control the European Corn Borer, a major corn pest. The extensive use of Bt-corn has led to concerns about the emergence of insect resistance. The United States Environment Protection Agency addressed this potential problem by developing an insect resistance management strategy, based, in part, on complex mathematical models using detailed biological assumptions about the population genetics and life history of the European Corn Borer. However, seed companies and others have sometimes used simpler deterministic profit models to justify the economics of Bt-corn to potential growers. Therefore an over reliance, by regulatory agencies, on complex modeling approaches may obscure the likely economic behavioral response of farmers who rely on these less complex models. However, the determinants of adoption are numerous, profit being one of them. We develop a simple model for the spread of resistance based on the logistic growth equation and use it to investigate the effect of uncertainty on farmer decisions to plant Bt-corn and follow EPA management rules. The model results suggest that planting Bt-corn is an optimal strategy under the type of uncertainty assumed in the model and that short-term economic behavior is likely to lead to the Environment Protection Agency management rules not being followed. Our results add weight to existing work on this problem. --Authors' Abstract